(untitled) (Tzintzun, Revista de Estudios Históricos, 2024)
The article analyzes historically and aesthetically the oil painting Military Action in Pueblo Viejo, 1829, by Carlos Paris, which represents the victory of the Mexican army over the Hispanic expedition, in its intention to reconquer the old New Spain, to determine it as a starting point for the construction of the heroic image of General Antonio López de Santa Anna, which -together with the epic narrative that permeated those years-, allowed him to constitute the preponderant political/ military figure of the first half of the Mexican nineteenth century: the human representation of the young nation.